Ovarian Sensitivity Decreased Significantly in Patients With Insulin Resistance Undergoing in vitro Fertilization and Embryo Transfer - Zheng, Yanjun; Pan, Ye; Li, Ping; Wang, Zhongyuan; Wang, Ze; Shi, Yuhua (Frontiers in Physiology, 2022)
Ovarian sensitivity could affect the outcome of in vitro fertilization and embryo transfer (IVF-ET). The objective of this study was to explore the relationship between the ovarian sensitivity index (OSI) and traditional ovarian response makers and observe the relationship between OSI and insulin resistance (IR). The patients enrolled in this study included 131 patients with polycystic ovary syndrome (PCOS) with IR (PCOS-IR), 52 patients with PCOS without IR (PCOS-N), 164 patients with control with IR (control-IR), 133 patients with control without IR (control-N), 295 patients with IR, 184 patients with non-IR, 183 patients with PCOS, and 297 patients with control (patients with non-PCOS). All patients received standard long protocol or the gonadotropin-releasing hormone (GnRH) antagonist protocol to induce follicular development. The two protocols downregulated the pituitary function or blocked the pituitary luteinizing hormone (LH) secretion with a GnRH antagonist. Both protocols can block premature LH surges because premature luteinization is not conducive to follicular development. All patients underwent IVF or intracytoplasmic sperm injection (ICSI). Embryo transfer was carried out according to the specific situation of each patient. The OSI was significantly reduced in patients with IR. The OSI had a significant positive relationship with anti-Müllerian hormone (AMH), antral follicle count (AFC), basal LH/follicle-stimulating hormone (FSH), dominant follicle number on trigger day, retrieved oocytes, embryo number, and high-quality embryo number. OSI had a significant negative relationship with age, body mass index (BMI), basal FSH, initial dose of Gn, and total dose of Gn. The receiver operating characteristic (ROC) curve of OSI demonstrated a better accuracy in distinguishing patients with positive pregnancy and clinical pregnancy, with an area under the curve (AUC) of 0.662 (95% CI, 0.598–0.727) and 0.636 (95% CI, 0.577–0.695), respectively. Patients could get a higher rate of dominant follicle count (p < 0.0001) through the treatment of standard long protocol when compared with GnRH antagonist protocol. The OSI has a significant correlation with traditional ovarian response markers and could be a good predictor of positive pregnancy and clinical pregnancy for patients with IR.